2013
DOI: 10.1111/zoj.12093
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary relationships among American mud crabs (Crustacea: Decapoda: Brachyura: Xanthoidea) inferred from nuclear and mitochondrial markers, with comments on adult morphology

Abstract: Members of the brachyuran crab superfamily Xanthoidea sensu Ng, Guinot & Davie (2008) are a morphologically and ecologically diverse assemblage encompassing more than 780 nominal species. On the basis of morphology, Xanthoidea is presently regarded to represent three families: Xanthidae, Pseudorhombilidae, and Panopeidae. However, few studies have examined this superfamily using modern phylogenetic methods, despite the ecological and economic importance of this large, poorly understood group. In this study we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 80 publications
1
26
0
3
Order By: Relevance
“…The present study builds upon previous efforts to clarify species composition and evolutionary relationships of American xanthoid crabs (Thoma et al 2009(Thoma et al , 2014Felder & Thoma 2010;Thoma & Felder 2012;Lasley et al 2013). It augments previously reported molecular genetic inferences with morphological findings to justify a family assignment and provides taxonomic descriptions at the generic and species level.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…The present study builds upon previous efforts to clarify species composition and evolutionary relationships of American xanthoid crabs (Thoma et al 2009(Thoma et al , 2014Felder & Thoma 2010;Thoma & Felder 2012;Lasley et al 2013). It augments previously reported molecular genetic inferences with morphological findings to justify a family assignment and provides taxonomic descriptions at the generic and species level.…”
Section: Introductionmentioning
confidence: 71%
“…Where shown, meters (m) indicate collection depths. GenBank accession numbers are as previously published by Thoma et al (2009Thoma et al ( , 2014, with the addition of equivalent USNM catalog numbers shown for the archived source specimens of extracted tissues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Thoma et al . ). Cyclodius paumotensis is also a much smaller species than S. flava or S. melanospinis .…”
Section: Discussionmentioning
confidence: 97%
“…() and Thoma et al . () showed that many eastern American xanthid genera now classified in the Euxanthinae, Actaeinae and Zosiminae actually form natural groups and likewise for Ratha . This ‘east American clade’ will also require revision.…”
Section: Discussionmentioning
confidence: 99%